2021
DOI: 10.1085/jgp.2021ecc19
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of Orai1 and SARAF in vascular remodeling

Abstract: Orai1 and STIM1, molecular components of store-operated calcium entry (SOCE), have been associated with vascular smooth muscle cell (VSMC) proliferation in vascular remodeling. Nevertheless, the role of SARAF (SOCE-associated regulatory factor), a regulatory protein involved in STIM1 inhibition, in vascular remodeling has not been examined. The aim of this study is to examine the role of SARAF and Orai1 in VSMC proliferation and neointima formation after balloon injury of rat carotid arteries. Experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was recently shown that the expression of SARAF was increased in balloon injured arteries along with STIM1 and Orai1. SARAF was shown to specifically regulate Orai1-mediated VMSC proliferation in response to balloon injury ( Martin-Bornez et al, 2022 ). Homer has also been shown to colocalize with STIM1/Orai1 and regulate Orai1-mediated VSMC proliferation and neointimal growth in the setting of balloon injured arteries ( Jia et al, 2017 ).…”
Section: Physiological and Pathophysiological Roles Of Stim/orai In T...mentioning
confidence: 99%
“…It was recently shown that the expression of SARAF was increased in balloon injured arteries along with STIM1 and Orai1. SARAF was shown to specifically regulate Orai1-mediated VMSC proliferation in response to balloon injury ( Martin-Bornez et al, 2022 ). Homer has also been shown to colocalize with STIM1/Orai1 and regulate Orai1-mediated VSMC proliferation and neointimal growth in the setting of balloon injured arteries ( Jia et al, 2017 ).…”
Section: Physiological and Pathophysiological Roles Of Stim/orai In T...mentioning
confidence: 99%